«Kids here go to school alone». Motherhood in the crossroads of Peruvian migrants in Aichi, Japan - Matsumura, Akemi (2019)
After more than 20 years of the first massive migrations of Peruvians to Japan, Peruvian women face challenges in raising the second generation of migrants in this country. In this context, this research tries to answer how these women redefine their motherhood. The migratory routes of women, their relationship between households, work and school are key in this reconceptualization. Thus, this article shows that their migratory motivations, their gender roles as mothers and wives, and the different upbringings of their children are the main factors that question their concepts of motherhood as guiding mothers. This paper is based on a qualitative research, elaborated under an ethnographic methodology, carrying out fieldwork with Peruvian mothers living in Aichi prefecture, Japan between 2016 and 2017.